Prevalence, determinants and impact of urinary incontinence on quality of life among Palestinian postpartum women: a cross-sectional study - Zaher Nazzal; Bayan Hersh; Rawan Shaban (BMJ Open)
Objectives Urinary incontinence (UI) is prevalent among women, particularly during the postpartum period, impacting various aspects of quality of life (QoL). The objectives of this study are to determine the prevalence of postpartum UI among Palestinian women, explore its relationship with delivery mode, identify associated risk factors and assess its impact on QoL.Design A cross-sectional study.Setting and participants The study targeted postpartum women attending primary healthcare centres in the North West Bank of Palestine. Data were collected using interviewer-administered questionnaires. The primary outcome was the prevalence of postpartum UI, and the secondary outcomes included risk factors associated with UI and its impact on QoL. We used multivariate logistic regression analysis to identify factors associated with UI while adjusting for confounding variables. The Institutional Review Board of An-Najah National University approved the study.Results Out of 507 participants, 13.6% (95% CI 10.8% to 16.9%) experienced postpartum UI, with 78.3% reporting moderate-to-severe symptoms. Maternal body mass index (BMI) (adjusted OR (aOR) 1.98; 95% CI 1.1 to 3.7; adjusted p=0.033) and experiencing UI during the last pregnancy (aOR 2.25; 95% CI 1.3 to 3.8; adjusted p=0.003) were significant risk factors for postpartum UI. No significant association was found between the normal vaginal delivery and postpartum UI compared with caesarean section (aOR 1.5; 95% CI 0.90 to 1.5; adjusted p=0.284). Postpartum UI severity significantly correlated with QoL, particularly in social embarrassment (p=0.005), psychosocial impact (p≤0.001) and avoidance and limiting behaviours (p≤0.001).Conclusion The prevalence of postpartum UI in Palestinian women is consistent with global findings. Experiencing UI during the last pregnancy and higher maternal BMI were identified as key risk factors for postpartum UI. These results highlight the need for early detection, intervention and preventive strategies to mitigate the impact of postpartum UI on QoL.